2015
DOI: 10.11114/ijsss.v3i6.1129
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Psychophysiological Potencies of Essential Oils, when Seen as a Function of Behavioral Task Assigned to the Participants after Inhalation

Abstract: To elucidate the psychophysiological effect of inhaling essential oils, in this paper, we sought to assess the following 12 essential oils: basil, bergamot, cardamom, cinnamon, juniper, lemon, orange, palmarosa, peppermint, sandalwood, spearmint, and ylang ylang. As these being target odors, we focused on the verbal (semantic) and non-verbal (skin temperature) endpoints of the stimuli. In our experimental design, we managed to assign different behavioral tasks to the participants. The Uchida-Kraepelin test was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The citrus scent was most intense near the hand washbasin and with distance the intensity decreased. The enormous diversity of perceptions of aroma stimuli leads to individual perception of smells which may result in different responses in behavior (Pellegrino et al, 2015; Sugawara et al, 2015). Pinto, Xavier, Calado, and Mariano (2014) have found, by measuring the electrical activity of the brain, that the human response to scent is highly subjective.…”
Section: Resultsmentioning
confidence: 99%
“…The citrus scent was most intense near the hand washbasin and with distance the intensity decreased. The enormous diversity of perceptions of aroma stimuli leads to individual perception of smells which may result in different responses in behavior (Pellegrino et al, 2015; Sugawara et al, 2015). Pinto, Xavier, Calado, and Mariano (2014) have found, by measuring the electrical activity of the brain, that the human response to scent is highly subjective.…”
Section: Resultsmentioning
confidence: 99%
“…Another major component, limonene, highly influenced the human autonomic nervous system parameters and mental conditions [43]. Recently, Sugawara et al [44] investigated the psychophysiological effect of 12 essential oils such as basil, bergamot, cardamom, cinnamon, juniper, lemon, orange, palmarosa, peppermint, sandalwood, spearmint, and ylang ylang. Based on the mental arithmetic and auditory tasks, the authors suggested that these essential oils may have versatile psychophysiological potencies.…”
Section: Discussionmentioning
confidence: 99%
“…Iannilli et al [104] investigated the electrophysiological response to food- and non-food-related odors in healthy volunteers and the analyses revealed the specific scalp potential maps for the two conditions. Sugawara et al [150] elucidated the psychophysiological effect of inhaling 12 different essential oils and suggested that essential oils may have versatile psychophysiological properties.…”
Section: Effect Of Inhalation Of Fragrance On Psychophysiological mentioning
confidence: 99%